Technology shocks, labour mobility and aggregate fluctuations - Daniela Hauser (Bank of Canada, 2014)
We provide evidence regarding the dynamic behaviour of net labour flows across U.S. states in response to a positive technology shock. Technology shocks are identified as disturbances that increase relative state productivity in the long run for 226 state pairs, encompassing 80 per cent of labour flows across U.S. states in the 1976 - 2008 period. The data suggest heterogeneous responses of both employment and net labour flows across states, conditional on a positive technology shock. We build a two-region dynamic stochastic general equilibrium (DSGE) model with endogenous labour mobility and region-specific shocks to account for this evidence. We calibrate the model economy consistently with the observed differences in the degree of nominal rigidities across states, and show that we replicate the different patterns of the responses in employment and net labour flows across states following a technology shock.
Keywords: E24; E32; J61; 330; Business fluctuations and cycles; Labour markets